2011
DOI: 10.1002/ange.201102156
|View full text |Cite
|
Sign up to set email alerts
|

Caprolactam from Renewable Resources: Catalytic Conversion of 5‐Hydroxymethylfurfural into Caprolactone

Abstract: Erneuerbares Nylon: 5‐Hydroxymethylfurfural (HMF), das aus erneuerbaren Quellen wie D‐Fructose zugänglich ist, wurde in nur drei Stufen mit einer sehr guten Gesamtselektivität in Caprolacton überführt. Dieser neue Ansatz umfasst zwei Hydrierungen, die 1,6‐Hexandiol liefern, und dessen oxidative Cyclisierung zu Caprolacton. Dieses wurde schließlich zu Caprolactam umgesetzt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 33 publications
2
71
0
1
Order By: Relevance
“…The current industrial process is based on the Ni-catalysed hydrocyanation of 1,3-butadiene. In our novel process, the desired product is obtained by selective oxidation of 1,6-hexanediol which can be derived from biomass 36 as shown in Fig. 3, in the presence of aq.…”
Section: Resultsmentioning
confidence: 99%
“…The current industrial process is based on the Ni-catalysed hydrocyanation of 1,3-butadiene. In our novel process, the desired product is obtained by selective oxidation of 1,6-hexanediol which can be derived from biomass 36 as shown in Fig. 3, in the presence of aq.…”
Section: Resultsmentioning
confidence: 99%
“…However, benzyl benzoate was isolated as the sole product as a result of an intermolecular condensation process; 1,5-pentanediol (Table 1, entry 7) was also dehydrogenated successfully to afford δ-valerolactone. Several research groups have previously reported homogeneous catalysts for the base-free oxidation of diols to lactones in the presence of a hydrogen acceptor, such as acetone (32)(33)(34)(35). However, reports related to the acceptorless conversion of the same are extremely rare in the literature (36)(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%
“…For example, recently, caprolactam has been prepared in a four-step process from 5-hydroxymethylfurfural (5-HMF) and ammonia. [4] Inspired by such research, we wondered whether amino-sugars could be used as precursors to new Ncontaining platform chemicals. Our initial studies in this area are presented herein.…”
Section: Introductionmentioning
confidence: 99%